Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/09273972.2016.1210173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical Success for Infantile Esotropia and Strabismus Associated with Neurological Impairment

Abstract: This study was unable to find the differences between surgical success rates in IE and strabismus associated with neurological impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In particular, a larger surgical effect per mm in children with developmental disorders has been reported, suggesting that, in these patients, under-correction is more likely to give better results [18][19][20][21]. However, in the scientific literature there is no consensus on the most suitable surgical dosage adjustment in these patients; and some authors noticed that reducing the amount of surgery in delayed children (mostly esotropic [22][23][24][25] but also exotropic [25]) to prevent overcorrection, is associated with a high rate of surgical failure, mainly due to undercorrection. Nevertheless, the same authors also observed that, on long term follow-up, some of these undercorrected esotropic patients drifted towards exotropia [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, a larger surgical effect per mm in children with developmental disorders has been reported, suggesting that, in these patients, under-correction is more likely to give better results [18][19][20][21]. However, in the scientific literature there is no consensus on the most suitable surgical dosage adjustment in these patients; and some authors noticed that reducing the amount of surgery in delayed children (mostly esotropic [22][23][24][25] but also exotropic [25]) to prevent overcorrection, is associated with a high rate of surgical failure, mainly due to undercorrection. Nevertheless, the same authors also observed that, on long term follow-up, some of these undercorrected esotropic patients drifted towards exotropia [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…This approach results from the adaptation of the nomograms proposed in the scientific literature to our personal experience and is superimposable to the guidelines by Taylor et al [32]. As precise strabismus assessment and surgical planning is often challenging in AS patients, especially in subjects with greater deviations, and considering the exaggerated response to standard amounts of surgery [21] and the risk of consecutive strabismus on long term follow-up [22][23][24][25] reported by previous studies, we applied a small reduction of the amount of surgery to correct esotropia and a greater reduction to correct exotropia (i.e. we performed only 8 mm bilateral LR recession for 45 PD exotropic correction).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Individual patients will have different visual development experiences, and therefore limiting the explanation for difference in outcomes only to muscle tone may be artificial. This explanation does not consider the impact of visual acuity, which is also known to be reduced in individuals with Down syndrome (Zahidi et al 2018), or of the presence or absence of binocular single vision which influence the surgical outcome (Kiziltunc et al 2016).…”
Section: Type Of Surgerymentioning
confidence: 99%
“…Surgeries to correct ET are reported to have successful outcomes in 48.5–89.7% of cases globally 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13. The large variability in success rates is due to differences in the post-operative angle from orthophoria used to assess outcome, the etiology of ET, the type of procedure, the length of post-operative follow-up, and other associated risk factors.…”
Section: Introductionmentioning
confidence: 99%